Non-drawing mattress spring package polyolefin hot melt adhesive and method of making same

By introducing microcrystalline wax and low molecular weight polypropylene into polyolefin hot melt adhesive to form a secondary crystalline network, and using epoxy-terminated polyolefin to improve compatibility, the problem of the inability to balance flowability and filament breakage performance of polyolefin hot melt adhesive in high-end mattress production is solved, achieving efficient spraying and stable bonding effect.

CN122628690APending Publication Date: 2026-08-25广东伟旺新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611145253.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing polyolefin hot melt adhesives cannot balance flowability and filament breakage resistance in high-end mattress production, resulting in low production efficiency and insufficient bonding strength, which affects mattress comfort and lifespan.

Method used

The combination of microcrystalline wax and low molecular weight polypropylene forms a secondary crystalline network, which improves the fluidity and initial bond strength of the adhesive. The epoxy-terminated polyolefin improves the compatibility of the components, ensuring uniform dispersion of the adhesive and achieving rapid fiber breakage and stable bonding.

Benefits of technology

It achieves simultaneous improvement in high fluidity and filament breakage, ensuring uniform coating and initial adhesion, adapting to the cycle requirements of high-speed production lines, and improving the production efficiency and service life of mattresses.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a non-stretching polyolefin hot melt adhesive for mattress spring wraps and its preparation method, belonging to the field of adhesives. First, microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin are mixed and melted to obtain a eutectic mixture. High-density polyethylene, polypropylene, epoxy-terminated polyolefin, and an antioxidant are mixed and melted, then added to the eutectic mixture. The mixture is then cooled and granulated. The polypropylene has a molecular weight of less than 80,000; the microcrystalline wax includes No. 70 and No. 90 microcrystalline waxes. The hot melt adhesive of this invention exhibits high fluidity and secondary gradient crystallization after hot melting. It has low viscosity at high temperatures, allowing for use with finer nozzles and higher spraying speeds. The adhesive line width is finer and more uniform, with no sagging. The secondary crystallization system ensures rapid fiber breakage without stringing after spraying and establishes sufficient bonding strength in a short time, improving spring positioning speed and meeting the long-term use requirements of mattresses under different temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a non-fraying polyolefin hot melt adhesive for mattress spring wrapping and its preparation method, belonging to the field of adhesives. Background Technology

[0002] In the production of high-end individually pocketed spring mattresses, the non-woven fabric encapsulation and bonding of the spring units is a core process. High-speed spraying equipment is commonly used for adhesive application, resulting in a fast production line cycle and stringent requirements for the stability of the hot melt adhesive spraying, curing speed, and bonding strength. Polyolefin hot melt adhesives have become the mainstream adhesive for spring wrapping due to their good aging resistance, wide range of bonding compatibility, and moderate cost. However, existing formulations have several shortcomings in practical applications that are difficult to balance, making them unsuitable for the production and use needs of high-end mattresses.

[0003] The most prominent problem with existing polyolefin hot melt adhesives is the inability to simultaneously achieve good flowability and filament breakage performance. To adapt to high-speed spraying conditions, formulations often improve flowability by reducing the system viscosity. However, after the viscosity decreases, the cohesive strength of the adhesive is insufficient, and the adhesive filaments cannot break quickly after leaving the nozzle. A large number of thin and long adhesive filaments scatter and accumulate around the machine tool guide rail and nozzle, requiring frequent machine stops for cleaning, which directly reduces production efficiency. On the other hand, if the system viscosity is increased to improve the filament breakage effect, it will lead to insufficient flowability of the adhesive, resulting in large fluctuations in the width of the sprayed adhesive lines. When applying adhesive to an inclined nonwoven fabric surface, the adhesive layer is prone to sagging, causing problems such as excessively thick adhesive layers in some areas and missed adhesion. This significantly reduces the bonding yield of spring packs.

[0004] Furthermore, the existing formula has a slow initial bond strength development. In high-speed production lines, the springs need to enter the next process shortly after positioning. If the adhesive has not formed sufficient cohesive strength and interfacial adhesion, the springs are prone to shifting within the nonwoven fabric, leading to deviations in the spring pack size. Ultimately, this results in uneven pressure on the mattress, affecting both comfort and lifespan. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, the present invention provides a non-fraying polyolefin hot melt adhesive for mattress spring wrapping and its preparation method, which is easy to break after spraying and has strong initial adhesion.

[0006] The technical solution adopted by this invention to solve its technical problem is: In a first aspect, this application provides a method for preparing a non-fraying polyolefin hot melt adhesive for mattress spring packs, the steps of which include: Microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin are mixed and heated to melt to obtain a eutectic mixture; the microcrystalline wax includes No. 70 microcrystalline wax and No. 90 microcrystalline wax. High-density polyethylene, polypropylene, epoxy-terminated polyolefin, and antioxidant are mixed, heated and stirred until completely melted, and then the eutectic mixture is added to obtain a mixed adhesive; the molecular weight of the polypropylene is less than 80,000. The mixed adhesive is cooled and granulated to obtain the non-fiberized polyolefin hot melt adhesive for mattress spring wrapping.

[0007] During application, the microcrystalline wax forms fine crystal nuclei during the cooling process of the adhesive, constructing a temporary physical network that rapidly enhances the cohesive strength of the melt. This allows the adhesive filaments to acquire sufficient cohesive force quickly after leaving the nozzle, resulting in clean filament breakage and preventing stringing. The low molecular weight polypropylene reduces the overall viscosity of the adhesive, improves high-temperature fluidity, ensures uniform adhesive line width during spraying, and reduces sagging. The microcrystalline network also serves as an early strength framework, allowing the adhesive layer to possess a certain adhesive strength before complete curing, accelerating the establishment of initial adhesion, and adapting to the high-speed assembly production rhythm of spring packs. Overall, this achieves a simultaneous improvement in fluidity, filament breakage resistance, and initial tack.

[0008] Furthermore, the poor dispersion uniformity of tackifying resins (hydrogenated C5-C9 copolymer petroleum resins), waxes, and other components in the polyolefin matrix can cause local viscosity differences in the adhesive. The method in this application introduces epoxy-terminated polyolefins to improve the compatibility between the polyolefin matrix and these components. Even with hydrogen saturation, industrial-grade resins inevitably retain trace amounts of polar impurities, such as hydroxyl, carboxyl, or ester groups, originating from oxidation side reactions during polymerization or catalyst residues. Epoxy-terminated polyolefins can entangle with the polyolefin matrix and co-crystallize, while the epoxy groups react with polar impurities or generate strong interactions. The combined effect of these two actions reduces interfacial tension, allowing tackifying resins and other components to be uniformly dispersed in the matrix as finer particles. A uniformly dispersed system exhibits more stable rheological properties, consistent adhesive viscosity during spraying, uniform adhesive line width, stable filament breakage without stringing, and reduced filament accumulation on the machine tool.

[0009] Further, by weight, the raw materials include 15 to 22 parts of the high-density polyethylene, 25 to 35 parts of the polypropylene, 10 to 16 parts of the microcrystalline wax, 22 to 30 parts of the hydrogenated C5-C9 copolymer petroleum resin, 2 to 5 parts of the epoxy-terminated polyolefin, and 0.2 to 0.4 parts of the antioxidant.

[0010] Appropriate amounts of high-density polyethylene provide the basic cohesive strength of the adhesive layer, preventing it from softening and deforming at room or high temperatures, and ensuring long-term bonding effectiveness. Controlling the polypropylene content stabilizes the system's melt viscosity within a range suitable for high-speed spraying, ensuring smooth extrusion and uniform adhesive lines. Excessive polyolefin content can over-dilute the wax phase's crystalline network. A suitable amount of microcrystalline wax forms a continuous temporary crystalline network as the adhesive cools, ensuring fast fiber breakage and early strength. Insufficient wax leads to insufficient nucleus density, slow fiber breakage response, and inability to completely resolve fiber pulling issues. Excessive wax weakens the final cohesive strength of the adhesive layer, reducing bond durability and making the adhesive layer prone to cracking after prolonged spring compression.

[0011] Furthermore, in the microcrystalline wax, the mass ratio of No. 70 microcrystalline wax to No. 90 microcrystalline wax is 1:1~2. In the initial cooling stage, it can provide a sufficient number of crystal nuclei to quickly build a continuous temporary physical network. The cohesive strength of the adhesive filament rises to the fracture threshold in a very short time after leaving the nozzle, achieving clean filament breakage without any stringing or trailing. The secondary crystallization component allows the cohesive strength of the adhesive layer to continue to rise steadily after filament breakage, achieving sufficient initial bonding strength within seconds of application to withstand the external force after spring positioning and prevent the spring from slipping within the nonwoven fabric.

[0012] Further, before the step of adding the eutectic mixture, 0.5 to 1.2 parts by weight of ethylene-methyl acrylate copolymer are added.

[0013] Further, before the step of adding the eutectic mixture, 0.4 to 1.0 parts by mass of dicumyl peroxide are added.

[0014] Furthermore, in the step of mixing the microcrystalline wax and the hydrogenated C5-C9 copolymer petroleum resin, 0.8 to 1.5 parts by weight of dibenzyl sorbitol are also added.

[0015] Furthermore, in the step of mixing microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin, 0.2 to 0.5 parts of talc powder are added by weight.

[0016] Furthermore, in the step of mixing microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin and heating to melt, the maximum heating temperature is 95℃~110℃.

[0017] At this temperature, the viscosity of the eutectic mixture is within a suitable range. After being added dropwise to the high-temperature matrix (polyolefin), it can be quickly sheared and dispersed into fine particles by the matrix, shortening the subsequent stirring time and reducing the thermo-oxidative aging time of the polyolefin matrix. Combined with the high-temperature environment of the melting matrix, the temperature difference between the eutectic mixture and the matrix is ​​controlled within a reasonable range, and its addition will not cause local cooling and crystallization of the matrix, ensuring the overall homogeneity of the system.

[0018] Furthermore, in the step of mixing high-density polyethylene, polypropylene, epoxy-terminated polyolefin, and antioxidant, and heating and stirring, the heating temperature is 160℃~170℃, and the stirring speed is 100rpm~150rpm.

[0019] This temperature allows high-density polyethylene and polypropylene to completely melt, forming a homogeneous matrix phase while ensuring the activity of the epoxy-terminated polyolefin, which can fully exert its compatibilizing effect when it comes into contact with the dispersed phase later. The mild processing conditions allow antioxidants to work fully, reducing thermal aging during processing, resulting in lighter granule color and better aging resistance during long-term use. Even after many years of use, the adhesive layer of the mattress can still maintain sufficient bonding strength.

[0020] Secondly, this application provides a non-stretching polyolefin hot melt adhesive for mattress spring wrapping, which is made by the method for preparing the non-stretching polyolefin hot melt adhesive for mattress spring wrapping described in the first aspect.

[0021] The beneficial effects of this invention are: the non-stretching polyolefin hot melt adhesive for mattress spring wrapping has high fluidity and secondary gradient crystallization characteristics after hot melting, low viscosity at high temperatures, can be adapted to finer nozzles and higher spraying speeds, and produces finer and more uniform adhesive lines without sagging. The secondary crystallization system ensures rapid fiber breakage and no stringing after spraying, while also establishing sufficient bonding strength in a short time. The spring positioning speed is improved, which can meet the long-term use requirements of mattresses under different temperature environments. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this invention.

[0023] It should be understood that, without conflict, any and all embodiments of the present invention can be combined with technical features of any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes such combinations to obtain other embodiments.

[0024] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail.

[0025] This application provides a method for preparing a non-fraying polyolefin hot melt adhesive for mattress spring wraps, the steps of which include: S1: Mix microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin, heat to melt, and obtain a eutectic mixture. The microcrystalline wax includes No. 70 microcrystalline wax and No. 90 microcrystalline wax.

[0026] S2: High-density polyethylene, polypropylene, epoxy-terminated polyolefin, and antioxidant are mixed, heated, and stirred until completely melted. Then, a eutectic mixture is added to obtain a mixed adhesive. The molecular weight of polypropylene is less than 80,000.

[0027] S3: Cool and granulate the mixed adhesive to obtain a non-stringy polyolefin hot melt adhesive for mattress spring wrapping.

[0028] During the cooling process of the adhesive, the component that reaches the crystallization temperature first rapidly forms fine crystal nuclei and builds a temporary physical network. This allows the cohesive strength of the adhesive filaments to increase rapidly shortly after leaving the nozzle, resulting in clean filament breakage and reducing filament pulling and adhesive buildup on the machine tool. The component that reaches the crystallization temperature later gradually crystallizes during the subsequent cooling stage, filling the gaps in the temporary network and continuously improving the cohesive strength of the adhesive layer. This promotes the steady establishment of initial adhesion and prevents slippage after spring positioning. Low molecular weight polypropylene lowers the overall melt viscosity of the system, improving high-temperature flow properties. The adhesive is extruded smoothly through the nozzle, resulting in a uniform spray line width. When applied to an inclined nonwoven fabric surface, it is less prone to sagging, reducing localized excessive adhesive layer thickness or missed adhesion. Epoxy-terminated polyolefins are distributed at the phase interface between the matrix and the dispersed phase. One end is entangled with the polyolefin molecular chain, and the other end is combined with residual polar groups, reducing interfacial tension and resulting in finer and more uniform dispersed phase particles. This further stabilizes the rheological properties of the system and reduces the release of small molecule components.

[0029] The low viscosity of low molecular weight polypropylene would normally weaken fiber breaking performance, but the graded crystallization of microcrystalline wax quickly replenishes cohesive strength, breaking the inherent contradiction that flow and fiber breaking cannot be simultaneously achieved. Microcrystalline wax alone is prone to uneven dispersion, but the pre-melting process combined with the compatibilizing effect of epoxy-terminated polyolefins ensures uniform dispersion of the wax component, continuous and complete crystallization network, and stable and controllable fiber breaking effect. Hydrogenated C5-C9 copolymer petroleum resin is distributed synchronously with the dispersed phase to all parts of the adhesive layer, and quickly impregnates the nonwoven fibers after application. Combined with the early strength skeleton of the microcrystalline network, the initial bonding strength is quickly established, and it can withstand the external force of spring positioning without waiting for the adhesive layer to fully cure, which is suitable for the fast cycle requirements of high-speed production lines.

[0030] In the high-temperature molten state, the non-polar components other than the epoxy-terminated polyolefin do indeed appear to have good compatibility, mixing into a homogeneous and transparent liquid. However, the final properties of hot melt adhesives depend on their structure in the solid state at room temperature, not on the macroscopic mixing in the high-temperature liquid state. This is why, even if the adhesive consists entirely of non-polar substances, the epoxy-terminated polyolefin must still be introduced. Without the epoxy-terminated polyolefin, the resin and wax would agglomerate into large macroscopic droplets, appearing whitish and cloudy within the adhesive particles. This phase separation leads to stress concentration within the adhesive layer, causing cracks to propagate along the phase interface during stretching.

[0031] Specifically, the preparation steps are as follows: Raw material composition (parts by weight): 15-22 parts high-density polyethylene, 25-35 parts low molecular weight polypropylene, 10-16 parts microcrystalline wax (70#:90#=1:1~2), 22-30 parts hydrogenated C5-C9 copolymer petroleum resin, 2-5 parts epoxy-terminated polyolefin, and 0.2-0.4 parts antioxidant.

[0032] First, the compounded microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin are mixed in proportion, heated to 95℃~110℃ and stirred evenly to obtain a eutectic mixture, which is then kept warm for later use.

[0033] Then, high-density polyethylene, low molecular weight polypropylene, epoxy-terminated polyolefin, and antioxidant are added to the reactor, heated to 160~170℃, and stirred until completely melted at a stirring speed of 100~150 rpm. Under the condition of heat preservation, the above eutectic mixture is slowly added, and stirring is continued for 15~20 minutes to obtain a uniformly mixed adhesive.

[0034] The mixed adhesive is fed into a steel belt granulator, cooled and cured to form hemispherical granules, which are the finished product.

[0035] High-density polyethylene (HDPE) and low-molecular-weight polypropylene (LMPP) serve as the composite matrix. HDPE enhances the cohesive strength and temperature resistance of the adhesive layer, while the high proportion of LPP ensures excellent flowability, making it suitable for demanding spraying conditions. The compounded microcrystalline wax contains components with high and low melting points, forming a secondary crystallization gradient, resulting in better fiber breakage and initial tack. Hydrogenated C5-C9 copolymer petroleum resin balances compatibility and cohesive strength, providing more balanced adhesion. The epoxy groups of the epoxy-terminated polyolefin can react with trace amounts of hydroxyl and carboxyl groups in the resin, resulting in a more stable compatibilizing effect and a smaller dispersed phase size. In terms of dosage, LPP has the highest proportion to ensure flowability; 10-16 parts of the compounded microcrystalline wax are sufficient to form effective secondary crystallization. In terms of process, the reactor blending process has a mild shear, suitable for high-flow systems. A temperature of 160-170℃ ensures that all components fully melt and react, and a stirring time of 15-20 minutes ensures system homogeneity.

[0036] In a preferred embodiment, before adding the eutectic mixture, step S2 involves adding 0.5 to 1.2 parts by weight of ethylene-methyl acrylate copolymer.

[0037] The methyl acrylate groups of ethylene-methyl acrylate can react with epoxy-terminated oligomers, expanding the bonding force at the compatibilizing interface. Simultaneously, its polyolefin segments are fully entangled with low molecular weight polypropylene, constructing a denser compatibilizing network that firmly locks in the microcrystalline wax molecules. After long-term storage at room temperature, the amount of surface blooming (actually small molecule precipitation) of the granules decreases, and the melt flowability remains essentially unchanged, preventing nozzle clogging issues.

[0038] During long-term use of a mattress, the repeated compression of the springs generates alternating shear forces, causing the overall adhesive strength of the glue layer to slowly decrease over time. Therefore, preferably, in step S2, before adding the eutectic mixture, 0.4 to 1.0 parts by weight of dicumyl peroxide are added.

[0039] Trace amounts of peroxide can enhance the grafting reaction between ethylene-methyl acrylate, epoxy oligomers, and the polyolefin matrix, resulting in a longer fatigue life of the adhesive layer under long-term alternating stress. The grafting degree of this reaction is extremely low, and it does not form an overall cross-linked structure; therefore, the melt flowability and crystallization properties of the adhesive are essentially unaffected.

[0040] In a preferred embodiment, step S1 further includes 0.8 to 1.5 parts by weight of dibenzylidene sorbitol. Dibenzylidene sorbitol can specifically induce heterogeneous nucleation of microcrystalline phases at a high melting point of 90°C, refine grain size, and simultaneously raise the initial crystallization temperature of the high-melting-point component, widening the time difference between the two stages of crystallization and making the layered crystallization clearer. When the ambient temperature fluctuates within the range of 15 to 35°C, the filament breaking speed fluctuates less, ensuring sufficient wetting and achieving the required initial adhesion at low temperatures, while also ensuring crisp filament breaking without tailing at high temperatures, making it suitable for workshop production environments in different seasons.

[0041] In the examples where dibenzyl sorbitol was added, the crystallization nuclei were concentrated only within the dispersed phase (microcrystalline wax), and the polyolefin matrix phase lacked effective crystal nuclei, resulting in larger crystal grain sizes. Accordingly, 0.2 to 0.5 parts by weight of talc powder, especially ultrafine talc powder, were also added in step S1.

[0042] Ultrafine talc can refine the crystal grains of the polyolefin matrix, allowing the crystal size of the matrix phase and the dispersed phase to match, significantly improving overall crystal uniformity. During high-speed spraying, there is no longitudinal splitting of the adhesive lines, the broken ends are clean and burr-free, and the cleanliness of the broken ends is significantly improved, leaving no fine adhesive debris on the machine tool. The extremely low amount of talc added will not affect the fluidity or appearance of the adhesive, nor will it damage the compatibilizing network or secondary crystal structure.

[0043] Example 1 Raw materials (parts by weight): 18 parts high-density polyethylene (Dushanzi Petrochemical HDPEDMDA-8008), 30 parts low molecular weight polypropylene (Licocene™ PP1602, Clariant), 5 parts 70℃ microcrystalline wax (Sinopec 70# microcrystalline wax), 5 parts 90℃ microcrystalline wax (Sinopec 90# microcrystalline wax), 26 parts hydrogenated C5-C9 copolymer petroleum resin (FUCLEARFU-100), 3.5 parts epoxy-terminated polyolefin (LOTADERAX8840, SK Korea), and 0.3 parts antioxidant 1010 (BASF).

[0044] Preparation steps: Microcrystalline wax and petroleum resin are mixed, heated to 100°C to melt and stir evenly, and kept at the temperature for 5 minutes to obtain a eutectic mixture.

[0045] HDPE, low molecular weight PP, epoxy-terminated polyolefin, and antioxidant are added to the reactor, heated to 165°C, and stirred at 120 rpm until completely melted and mixed. The eutectic mixture is then added dropwise over 8 minutes, followed by stirring for another 18 minutes after the addition is complete.

[0046] The adhesive was degassed under vacuum at -0.085 MPa for 3 minutes, and then fed into a steel belt granulator for air-cooled granulation to obtain the hot melt adhesive of Example 1.

[0047] Example 2 The difference between Example 2 and Example 1 is that Example 2 contains 0.8 parts of ethylene-methyl acrylate copolymer (Dow EMA1125AC), while the other raw materials are the same as in Example 1.

[0048] Preparation steps: Microcrystalline wax and petroleum resin are mixed, heated to 95°C to melt and stir evenly, and kept at the temperature for 5 minutes to obtain a eutectic mixture.

[0049] HDPE, low molecular weight PP, epoxy-terminated polyolefin, antioxidant, and ethylene-methyl acrylate copolymer are added to a reactor. The mixture is heated to 160°C and stirred at 110 rpm until completely melted and mixed. The eutectic mixture is then added dropwise over 8 minutes, followed by stirring for another 18 minutes after the addition is complete.

[0050] -0.085MPa vacuum degassing for 3 minutes, the adhesive solution is fed into a steel belt granulator for air cooling granulation to obtain the hot melt adhesive of Example 2.

[0051] Example 3 The difference between Example 3 and Example 2 is that 0.4 parts of dicumyl peroxide were added to the raw materials, and the timing of addition was the same as that of ethylene-methyl acrylate copolymer. The rest of the operation was the same as that of Example 2, and the hot melt adhesive of Example 3 was obtained.

[0052] Example 4 The difference between Example 4 and Example 1 is that 1.2 parts of dibenzyl sorbitol are added; the other raw materials are the same as in Example 1.

[0053] Preparation steps: Microcrystalline wax is mixed with petroleum resin and dibenzyl sorbitol, heated to 105°C to melt and stir evenly, and kept at the temperature for 5 minutes to obtain a eutectic mixture.

[0054] HDPE, low molecular weight PP, epoxy-terminated polyolefin, and antioxidant are added to the reactor, heated to 160°C, and stirred at 130 rpm until completely melted and mixed. The eutectic mixture is then added dropwise over 8 minutes, followed by stirring for another 18 minutes after the addition is complete.

[0055] The adhesive was degassed under vacuum at -0.085 MPa for 3 minutes, and then fed into a steel belt granulator for air-cooled granulation to obtain the hot melt adhesive of Example 4.

[0056] Example 5 The difference between Example 5 and Example 4 is that 0.3 parts of ultrafine talc powder (Guilin Guiguang 1250 mesh) were added to the raw materials. The timing of addition was the same as that of dibenzyl sorbitol. The rest of the operation was the same as that of Example 4, and the hot melt adhesive of Example 5 was obtained.

[0057] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the raw materials do not contain microcrystalline wax, while the rest of the operation is the same as in Example 1, and the hot melt adhesive of Comparative Example 1 is obtained.

[0058] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the raw materials do not contain epoxy-terminated polyolefins. The rest of the operation is the same as that in Example 1, and the hot melt adhesive of Comparative Example 2 is obtained.

[0059] The following tests were performed on the hot melt adhesives of each embodiment and comparative example: Melt viscosity: Refer to GB / T2794-2022 "Determination of viscosity of adhesives - Single cylinder rotation viscometer method", test temperature 160℃.

[0060] T-Peel Strength: Refer to ASTM D1876-08(2023) "Standard Test Method for Peel Resistance of Adhesives (T-Peel Test)". The substrate is 20g / m² PP nonwoven fabric, cut into strips of 25.4mm × 300mm. Two pieces of nonwoven fabric are bonded together with an adhesive application rate of 30g / m², with an overlap length of 12.5±0.5mm, leaving unbonded areas at both ends for clamping. The samples are equilibrated at 23±2℃ and 50±5% RH for at least 48 hours. The unbonded ends of the samples are bent into a T-shape and clamped in the upper and lower clamps of a universal tensile testing machine. Peeling is performed at a constant speed of 127mm / min. The average peel force during the stable peeling stage is recorded, and the T-peel strength per unit width (N / cm) is calculated. Five valid samples are tested for each formulation, and the average value is taken.

[0061] Blooming level: The industry-standard visual rating method is adopted. The rating is determined after 30 days of storage at a constant temperature of 60℃ (0 for no blooming, 5 for severe blooming).

[0062] The experimental results are shown in Table 1.

[0063] Other coating properties, such as broken wire length, glue line deviation, fatigue resistance, and broken wire burrs, were tested under the customized conditions of mattress spring wrapping glue application. The test results are shown in Table 2, based on industrial 0.5MPa pressure spraying conditions.

[0064] The percentage of burrs on the broken filament cross-section refers to the total length of the fine filamentous protrusions (burrs) with a length ≥0.1mm extending from the edge of the broken filament after hot melt adhesive spraying, out of the total perimeter of the cross-section. It is used to characterize the neatness of the filament breakage; the lower the value, the cleaner and crisper the filament breakage, and the less likely it is to produce fine adhesive debris accumulation. Twenty independent broken filaments were randomly selected from each sample for measurement, and the arithmetic mean was taken as the final result.

[0065] The 10-meter adhesive line width deviation rate refers to the percentage of the maximum fluctuation range of the width of a 10-meter-long adhesive line sprayed continuously under fixed spraying conditions relative to the average width of the adhesive line. It is used to characterize the uniformity of adhesive spraying. The lower the value, the better the consistency of the adhesive line thickness. When applying adhesive to an inclined surface, it is less likely to cause problems such as local excessive thickness and dripping or local excessive thinness and missed adhesion.

[0066] The 15℃ / 35℃ environmental filament length fluctuation ratio refers to the percentage difference in filament length under two typical environmental temperatures: a low-temperature workshop in winter (15℃) and a high-temperature workshop in summer (35℃), relative to the filament length at room temperature (25℃). It is used to characterize the filament breaking performance's tolerance to environmental temperature fluctuations. The lower the value, the better the temperature adaptability and the more stable the filament breaking effect during production in different seasons.

[0067] The bond strength retention rate after 100,000 compression cycles refers to the ratio of the remaining bond strength to the initial bond strength after a specified number of compression cycles, simulating the actual long-term repeated compression of mattress springs. It characterizes the fatigue resistance of the adhesive layer under alternating stress; a higher value indicates better bonding reliability under long-term use and a longer mattress lifespan. Compression cycle conditions: The sample is fixed in a repeated compression testing machine, the compression amount is 30% of the original spring length, the compression frequency is 1Hz, and 100,000 cycles are performed continuously at room temperature.

[0068] Table 1 Melt viscosity at 160℃ (mPa·s) 1520 1480 1550 1500 1530 1210 2260 Length of broken wire at room temperature (mm) 18 17 18 16 15 122 36 T-peel strength (N / cm) 1.5 1.6 1.7 1.4 1.5 0.5 1.0 Blooming rating (0-5) after 30 days of storage at 60℃ 3 1 1 3 3 2 4 Table 2 Bond strength retention rate after 100,000 compressions (%) 71 75 92 70 72 65 62 Fluctuation ratio of broken wire length at 15℃ / 35℃ environments (%) 23 22 21 7 6 31 42 Width deviation rate of 10-meter adhesive line (%) 4.3 4.1 4.2 4.0 3.8 6.8 11.7 Percentage of burrs on broken wire cross-section (%) 18 17 18 19 2.5 22 35 Comparative Example 1, which does not contain microcrystalline wax, has the lowest melt viscosity and best flowability, but its broken fiber length is large and its initial peel strength is low, completely failing to meet the requirements of no fiber breakage and rapid positioning. This proves that the low-viscosity adhesive without a secondary crystalline framework cannot build up cohesive strength quickly enough to support rapid fiber breakage. Comparative Example 2, which does not contain epoxy-terminated polyolefin, has high melt viscosity, large glue line width deviation rate, and large fiber breakage fluctuations. This indicates that epoxy-terminated polyolefin can reduce interfacial tension, allowing wax and resin to be uniformly dispersed in the matrix and stabilizing the rheological properties of the system. These examples break the inherent contradiction between the traditional polyolefin hot melt adhesive's flowability and fiber breakage performance, achieving high flowability, no fiber breakage, high initial tack, and uniform glue line.

[0069] In Example 2, after introducing ethylene-methyl acrylate copolymer, the core flow, fiber breakage, and initial tack properties were basically the same as in Example 1. The blooming level was reduced after 30 days of storage at 60°C, and the anti-exudation performance was greatly improved.

[0070] In Example 3, after adding a trace amount of dicumyl peroxide, the adhesive strength retention rate after 100,000 repeated compressions was improved, and other properties did not fluctuate significantly. This indicates that the grafting only occurs at the phase interface and to a low degree, and will not form overall cross-linking. Therefore, the fluidity and crystallization properties of the adhesive are not affected at all, and the adhesive life of the mattress can be significantly extended after long-term use.

[0071] In Example 4, after adding dibenzyl sorbitol nucleating agent, the filament length fluctuation ratio at 15°C and 35°C was lower, and the temperature adaptability was significantly improved.

[0072] In Example 5, the addition of ultrafine talc resulted in a lower proportion of burrs on the broken filament cross-section and a further decrease in the deviation rate of adhesive line width. This indicates that ultrafine talc, as a nucleating agent in the matrix phase, can refine the crystalline grains of the polyolefin matrix, allowing the crystal sizes of the two phases to match, significantly improving the overall crystal uniformity and eliminating mechanical anisotropy.

[0073] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, material, or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0074] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a non-fraying polyolefin hot melt adhesive for mattress spring wrapping, characterized in that the steps include... include: Microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin are mixed and heated to melt to obtain a eutectic mixture; the microcrystalline wax includes No. 70 microcrystalline wax and No. 90 microcrystalline wax. High-density polyethylene, polypropylene, epoxy-terminated polyolefin, and antioxidant are mixed, heated and stirred until completely melted, and then the eutectic mixture is added to obtain a mixed adhesive; the molecular weight of the polypropylene is less than 80,000. The mixed adhesive is cooled and granulated to obtain the non-fiberized polyolefin hot melt adhesive for mattress spring wrapping.

2. The method for preparing the non-filamentous mattress spring wrapping polyolefin hot melt adhesive according to claim 1, characterized in that, By weight, the raw materials include 15 to 22 parts of the high-density polyethylene, 25 to 35 parts of the polypropylene, 10 to 16 parts of the microcrystalline wax, 22 to 30 parts of the hydrogenated C5-C9 copolymer petroleum resin, 2 to 5 parts of the epoxy-terminated polyolefin, and 0.2 to 0.4 parts of the antioxidant.

3. The method for preparing the non-filamentous mattress spring wrapping polyolefin hot melt adhesive according to claim 2, characterized in that, In the microcrystalline wax, the mass ratio of No. 70 microcrystalline wax to No. 90 microcrystalline wax is 1:1~2.

4. The method for preparing the non-fraying polyolefin hot melt adhesive for mattress spring wrapping according to claim 2, characterized in that, Before adding the eutectic mixture, 0.5 to 1.2 parts by weight of ethylene-methyl acrylate copolymer are added.

5. The method for preparing the non-fraying polyolefin hot melt adhesive for mattress spring wrapping according to claim 4, characterized in that, Before adding the eutectic mixture, add 0.4 to 1.0 parts by mass of dicumyl peroxide.

6. The method for preparing the non-filamentous mattress spring wrapping polyolefin hot melt adhesive according to claim 2, characterized in that, In the step of mixing microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin, 0.8 to 1.5 parts by weight of dibenzyl sorbitol were also added.

7. The method for preparing the non-fraying polyolefin hot melt adhesive for mattress spring wrapping according to claim 6, characterized in that, In the step of mixing microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin, 0.2 to 0.5 parts of talc powder were also added by weight.

8. The method for preparing the non-fraying polyolefin hot melt adhesive for mattress spring wrapping according to claim 1, characterized in that, In the step of mixing microcrystalline wax and hydrogenated C5-C9 copolymer petroleum resin and heating it to melt, the maximum heating temperature is 95℃~110℃.

9. The method for preparing the non-filamentous mattress spring wrapping polyolefin hot melt adhesive according to claim 1, characterized in that, In the step of mixing high-density polyethylene, polypropylene, epoxy-terminated polyolefin, and antioxidant, and heating and stirring, the heating temperature is 160℃~170℃, and the stirring speed is 100rpm~150rpm.

10. A non-fraying polyolefin hot melt adhesive for mattress spring wrapping, characterized in that, Made by the method for preparing non-fiber mattress spring packs using polyolefin hot melt adhesive as described in any one of claims 1 to 9.